SYNTHESIS OF POLYMERS HAVING N-HYDROXYMALEIMIDE UNITS BY THERMOLYSIS OF N-(ISOPROPYLOXYCARBONYLOXY)MALEIMIDE POLYMERS - AHN, KD; WILLSON, CG (KOREAN CHEMICAL SOC, 1995)
N-(Isopropyloxycarbonyloxy)maleimide (iPOCMI) has been synthesized and polymerized to give both the homopolymer and copolymers with substituted styrenes. These polymers were readily deprotected by thermolysis of the isopropyloxycarbonyl (iPOC) groups to provide the corresponding N-hydroxymaleimide (HOMI) polymers. The homopolymer and styrenic copolymers of iPOCMI were radically obtained in higher conversion and higher molecular weight than those obtained by direct polymerizations of N-hydroxymaleimide. The homopolymer of iPOCMI was transformed into poly(N-hydroxymaleimide)(PHOMI) by thermolysis of iPOC groups at 205 degrees C with concurrent release of propene and carbon dioxide. The copolymer of iPOCMI and styrene was thermally deprotected to the copolymer of HOMI and styrene at 235 degrees C. The mass loss was 28% and the T-g of the resulting copolymer was 250 degrees C. The thermal deprotection readily provided the desired, polar HOMI polymers which have T(g)s above 240 degrees C. The deprotection was accompanied by large changes in aqueous base solubility.
Keywords: COPOLYMERS